2013
DOI: 10.1016/j.compedu.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of pedagogical agent gender matching and learner choice on learning outcomes and perceptions

Abstract: The similarity attraction hypothesis posits that humans are drawn toward others who behave and appear similar to themselves. Two experiments examined this hypothesis with middle school students learning electrical circuit analysis in a computer -based environment with an Animated Pedagogical Agent (APA). Experiment 1 was designed to determine whether matching the gender of the APA to the student has a positive impact on learning outcomes or student perceptions. One hundred ninety-seven middle-school students l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 46 publications
2
35
1
1
Order By: Relevance
“…The latter would have the added benefit of giving students an extra opportunity of regulating their own study behaviour, which should increase feelings of autonomy and thereby possibly raise their motivation and self-efficacy (Bandura 2001;Behrend and Thompson 2012;Clark and Mayer 2011;Ryan and Deci 2000). A similar argument has previously been made in the animated pedagogical agent literature (Ozogul et al 2013). Because the gender of the model in a video modeling example does not seem to affect students' test performance, there seems to be no harm in providing students with the opportunity to choose the gender of their model, although future research should first examine whether our findings are replicated using tasks from other domains and over longer study periods.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The latter would have the added benefit of giving students an extra opportunity of regulating their own study behaviour, which should increase feelings of autonomy and thereby possibly raise their motivation and self-efficacy (Bandura 2001;Behrend and Thompson 2012;Clark and Mayer 2011;Ryan and Deci 2000). A similar argument has previously been made in the animated pedagogical agent literature (Ozogul et al 2013). Because the gender of the model in a video modeling example does not seem to affect students' test performance, there seems to be no harm in providing students with the opportunity to choose the gender of their model, although future research should first examine whether our findings are replicated using tasks from other domains and over longer study periods.…”
Section: Discussionmentioning
confidence: 71%
“…However, other research has shown that when learning an engineering task, often considered a stereotypically male domain in Western countries, interacting with a female model decreased women's beliefs about engineering stereotypes compared to interacting with a male agent (Rosenberg-Kima et al 2008). Moreover, when given the choice, students tend to select an agent of the same gender (Ozogul et al 2013).…”
Section: Model-observer Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the instructional effectiveness of onscreen pedagogical agents has been a topic of interest for the past 20 years (Cassell, 1Sullivan, Prevost, & Churchill, ; Dehn & van Mulken, ; Heidig & Clarebout, ; W. L. Johnson & Rickel, ; W. L. Johnson & Lester, ; Mayer & DaPra, ; R. Moreno et al, ; Schroeder & Adesope, ; Schroeder, Adesope, & Gilbert, ; Veletsianos & Russell, ; Wang, Li, Mayer, & Liu, ), an important remaining issue concerns how best to render the basic characteristics of the agent, such as gender, ethnicity, and age (Baylor & Kim, ; Hoogerheide, Loyens, & van Gog, ; Hoogerheide, van Mermeskerken, van Nassau, & van Gog, ; Kim & Baylor, ; R. Moreno & Flowerday, ; Ozogul, Johnson, Atkinson, & Reisslein, ; Rosenberg‐Kima, Plant, Doerr, & Baylor, ). Kim and Lim () found that learner gender was a significant factor in the learner's evaluations of a pedagogical agent with females holding more positive attitudes towards agents.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, future research should explore how a learner's demographic, cultural and personality markers may influence his or her perception of an agent's smile. Moreover, as suggested by the same reviewer, the findings of our study should be replicated with different agent designs (i.e., gender, role and ethnicity), in order to associate the effects of an agent's smile with agent properties such as gender (Ozogul, Johnson, Atkinson, & Reisslein, 2013;Wang & Yeh, 2013), stereotype (Liew, Tan, & Jayothisa, 2013;Veletsianos, 2010) and ethnicity (Kim & Wei, 2011;Moreno & Flowerday, 2006). Last but not least, a control group using the voice paired with static images of a smiling agent can be included in future experiments, in order to reinforce the validity of the current findings of this paper.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%